Como impulsionar a bioprospecç\~ao no Brasil: Bases para uma moderna regulaç\~ao do acesso a recursos genéticos e ao conhecimento tradicional associado - Nilo Luiz Saccaro Junior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– The theme of genetic resources and traditional knowledge associated with them, as well as the Brazilian leadership in related international debates, are increasingly important in current environmental issues. In order to this Brazilian leadership to continue, improvements in the country's legislation are required. This paper discusses some of the main conflicting points and the features that a national regulatory framework must have to overcome them. Simplicity and pragmatism are shown as prerequisites. Suggestions are based on three pillars: a new way to monitor bioprospectors, by encouraging legal activities; a diffuse distribution of benefits, with simple rules that allow capturing profits from bioprospecting; and synergy between the existence of traditional/indigenous communities and biodiversity maintenance.
Keywords: Q01; 330; biodiversity; genetic resources; bioprospecting; traditional knowledge